Religious Koplo Dangdut Music: Cultural Identity and Religious Expression - Arif Al Wasim; Handoyo Handoyo; Nurma Khusna Khanifa (Islamic Studies Journal for Social Transformation, 2019)
Humans and culture are two things that are interrelated and cannot be separated from each other. Religion and music are two things that have a relationship with culture. Religious messages and da'wah are often displayed in the packaging of musical art and bring religious music. The development of music in Indonesia in the past two decades gave rise to one of the dangdut music sub-genres, known as Koplo dangdut, which in its performance also often inserted religious messages and presented them in the religious Koplo dangdut format. This article examines Koplo dangdut as the cultural identity and religious expression of coastal communities, which is seen as a cultural reality, with an anthropological approach. The study is conducted with an ethical perspective, where the writer only observes without being directly involved in the object of observation. The main data in this study is the religious koplo dangdut music video from YouTube. Koplo dangdut, which is famous for its vulgarity and directness in the lyrics of the song, reflects the cultural conditions of the song performers with a background in coastal Javanese society. However, the religious side of the Koplo dangdut music genre still appears in the religious koplo dangdut sub-genre. Religious expressions that appear in the stage of religious koplo dangdut are artistic expressions which include dimensions of belief (ideology), experience (ahlak), and knowledge.